2021
DOI: 10.1101/2021.05.03.442133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human iPSC-derived brain endothelial microvessels in a multi-well format enable permeability screens of anti-inflammatory drugs

Abstract: Optimizing drug candidates for blood-brain barrier (BBB) penetration in humans remains one of the key challenges and many devastating brain diseases including neurodegenerative diseases still do not have adequate treatments. So far, it has been difficult to establish state-of-the-art human stem cell derived in vitro models that mimic physiological barrier properties including a 3D microvasculature in a format that is scalable enough to screen drugs for BBB penetration in early drug development phases. To addre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Then, functional assays have to be conducted to evaluate the angiogenic potential of hiPSC-ECs, such as their ability to form tube-like structures on Matrigel or hydrogel, and/ or to support vasculogenesis in vivo in xenograft models (DeCicco-Skinner et al, 2014;Orlova et al, 2014;Belair et al, 2016). Functional validation should also include assays for nitric oxide (NO) synthesis, low-density lipoprotein (LDL) incorporation, and for endothelial barrier function, such as transendothelial electrical resistance (TEER) or permeability assays using fluorescent tracers (Ritter et al, 2018;Goshi et al, 2019;Fengler et al, 2022). Moreover, hiPSC-ECs should respond to relevant stimuli, such as VEGF, by activating downstream signalling pathways involved in angiogenesis (Zachary, 2003).…”
Section: Generation and Validation Of Hipsc-ecsmentioning
confidence: 99%
“…Then, functional assays have to be conducted to evaluate the angiogenic potential of hiPSC-ECs, such as their ability to form tube-like structures on Matrigel or hydrogel, and/ or to support vasculogenesis in vivo in xenograft models (DeCicco-Skinner et al, 2014;Orlova et al, 2014;Belair et al, 2016). Functional validation should also include assays for nitric oxide (NO) synthesis, low-density lipoprotein (LDL) incorporation, and for endothelial barrier function, such as transendothelial electrical resistance (TEER) or permeability assays using fluorescent tracers (Ritter et al, 2018;Goshi et al, 2019;Fengler et al, 2022). Moreover, hiPSC-ECs should respond to relevant stimuli, such as VEGF, by activating downstream signalling pathways involved in angiogenesis (Zachary, 2003).…”
Section: Generation and Validation Of Hipsc-ecsmentioning
confidence: 99%
“…25,39 Also, previous work where TEER was monitored over the days of culture, showed significance difference in values due to the optimal incubation time for EC to develop TJs properly. 21,49 Moreover, several studies demonstrated that shear stress has a mechanotransductive effect that up-regulates the TJs expressions and RNA levels of BBB transporters. 50,51 As well, most BBB-oCs with applied shear stress showed higher electrical resistance (Figure 2E−H).…”
Section: ■ Teer Sensing In Bbb-ocmentioning
confidence: 99%
“…20,22,23 This fabrication approach is easier to industrialize than other configurations, which are currently commercialized by companies such as MIMETAS. 21 Usually, a positive electrode at the input and a negative electrode at the output are used for TEER measurements in this distribution (Figure 1C). The third arrangement in BBC-oC is based on tubular structures to mimic the cylindrical-like brain capillaries geometry based on the formation of hollow fibers as scaffolds that allows the tubular shape.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…hiPSC-derived BBB models may become an important tool for simulation of potential adverse responses in human BBB to FUS+MB, and identify co-treatments or settings that could attenuate these effects. The high-throughput potential of novel human BBB models [83,102] and applicability of FUS+MB in vitro [84] could also facilitate screening of various combinations of disease-targeting drug and adjuvant therapies alleviating effects of FUS in the context of distinct neurodegenerative diseases or underlying mutations, before clinical application. For example, glucocorticoids (GC) have known immunosuppressive effect and were shown to reduce brain edema and improve tightness of the BBB by upregulating expression of occludin, claudins and VE-cadherin [103].…”
Section: Human In Vitro Bbb Models Can Bridge the Gap Between Fus-med...mentioning
confidence: 99%